Concurrent Deterministic Execution Semantics for IEC 61499-Based OT–IT Convergence Industrial Edge Applications - Wenbin Dai; Shang Gao; Kaiyun Qin; Chuanyang Yu; Dongdong Zhang; Likuan Zhang; Hui Zhang (IEEE Open Journal of the Industrial Electronics Society)
Industrial edge computing provides new possibilities for traditional industrial automation systems. With massive computing, storage, and communication resources equipped with devices on the shop floor, a typical edge device can simultaneously handle multiple real-time and non-real-time tasks. Also, those tasks may include operation technologies, such as real-time control, and information technologies, such as data processing. Using a generic modeling language to design those new industrial edge applications becomes a challenge for site engineers. This paper proposes the IEC 61499 standard for operation and information technology convergence for industrial edge applications. The concurrent execution semantics of IEC 61499 function blocks are defined to support multiple applications simultaneously. The event scheduling rules are investigated to ensure the determinism of parallel executions of function block networks. Finally, a case study is provided for the performance analysis of the proposed concurrent execution semantics.